Polyphosphate dynamics at Station ALOHA, North Pacific subtropical gyre. (27th October 2015) - Diaz, Julia M.; Björkman, Karin M.; Haley, Sheean T.; Ingall, Ellery D.; Karl, David M.; Longo, Amelia F.; Dyhrman, Sonya T.
Abstract: Polyphosphate (polyP) was examined within the upper water column (≤ 150 m) of Station ALOHA (22° 45′N, 158° 00′W) during two cruises conducted in May–June 2013 and September 2013. Phosphorus molar ratios of particulate polyP to total particulate phosphorus (TPP) were relatively low, similar to previously reported values from the temperate western North Atlantic, and did not exhibit strong vertical gradients, reflecting a lack of polyP recycling relative to other forms of TPP with depth. Furthermore, relationships among polyP:TPP, soluble reactive phosphorus (SRP), and alkaline phosphatase activity (APA) were also consistent with previous observations from the Atlantic Ocean. To ascertain potential mechanisms of biological polyP production and utilization, surface seawater was incubated following nutrient additions. Results were consistent with polyP:TPP enrichment under opposite extremes of APA, suggesting diverse polyP accumulation/retention mechanisms. Addition of exogenous polyP (45 ± 5 P atoms) to field incubations did not increase chlorophyll content relative to controls, suggesting that polyP was not bioavailable to phytoplankton at Station ALOHA. To clarify this result, phytoplankton cultures were screened for the ability to utilize exogenous polyP. PolyP bioavailability was variable among model diatoms of the genus Thalassiosira, yet chain length did not influence polyP bioavailability. Thus, microbial community composition may influence polyP dynamics in the ocean, and vice versa.